Riverine Microplastics Pollution in Vietnam: A Review of Current Scientific Knowledge and Legal Policies - Truong Tran Nguyen, Sang; Strady, Emilie; Kieu Le, Thuy Chung; Le, Thi Minh Tam; Nguyen, Phuoc Dan; Pham, Ngoc Bao; Inamura, Yukako (Applied Environmental Research, 2023)
Plastic litter and microplastic pollution in the aquatic environment have become a major concern since scientists, politicians, and citizens began to learn about the impacts in recent years. This in-depth desk review of scientific papers and Vietnamese policies aims to state the current knowledge, legal framework, and action plan relative to microplastic assessment, release, and control in Vietnamese aquatic environments, especially rivers. Regarding scientific literature, this paper focuses on (i) the occurrence of microplastics in riverine surface water and sediments, (ii) the fate and transfer of microplastics in Vietnam’s canals-riverine- estuarine systems, (iii) their accumulation in biota, and (iv) effects to receiving river basins and human health through ingestion of seafood and salts. This paper also points out and describes the main and current Vietnamese policies on plastic litter, including microplastic, and the control of their release into the aquatic environment. Based on the needs identified from the scientific literature review and the action plan to be implemented in the near future, recommendations are given for both scientists and decision-makers to tackle microplastic pollution and provide a sustainable approach.